2014
DOI: 10.1021/es4040792
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Performance of Green Building Code and Certification Systems

Abstract: We examined the potential life-cycle environmental impact reduction of three green building code and certification (GBCC) systems: LEED, ASHRAE 189.1, and IgCC. A recently completed whole-building life cycle assessment (LCA) database of NIST was applied to a prototype building model specification by NREL. TRACI 2.0 of EPA was used for life cycle impact assessment (LCIA). The results showed that the baseline building model generates about 18 thousand metric tons CO2-equiv. of greenhouse gases (GHGs) and consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…While these certifications vary in terms of their emphasis on energy, water or indoor air quality, most definitions include some standard for energy and water efficiency. In an LCA of green building certifications, Suh et al (2014) constructed a parametric LCA model for a three storey commercial building and found that the environmental benefits achieved by energy savings during the use-phase of green buildings outweighed the impacts of additional insulation and other materials requirements for GHG emissions and most other impact categories. Our analysis builds on Suh et al (2014) using region-specific parameters.…”
Section: Green Commercial Buildingsmentioning
confidence: 99%
“…While these certifications vary in terms of their emphasis on energy, water or indoor air quality, most definitions include some standard for energy and water efficiency. In an LCA of green building certifications, Suh et al (2014) constructed a parametric LCA model for a three storey commercial building and found that the environmental benefits achieved by energy savings during the use-phase of green buildings outweighed the impacts of additional insulation and other materials requirements for GHG emissions and most other impact categories. Our analysis builds on Suh et al (2014) using region-specific parameters.…”
Section: Green Commercial Buildingsmentioning
confidence: 99%
“…A few studies have evaluated the influence of LEED on building LCA impacts (Suh et al. ; Humbert et al. ; Suzer ; Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some LEED scores did not yield a reduction of the overall LCA impacts (Al‐Ghamdi and Bilec ; Suh et al. ; Humbert et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Green building (GB), as one of the best practices of sustainable development in the construction industry, has drawn much attention [5][6][7][8]. Many researches of GB have been analyzed from different aspects, for example: Technological innovation [9][10][11], energy saving [12][13][14], risk management [15][16][17][18], influential factors for development [19][20][21], policy incentives and regulations [22][23][24], and economical benefit [25][26][27] etc.…”
Section: Introductionmentioning
confidence: 99%